The moderating effect of self-efficacy in the relationship between perceived job characteristics and work engagement / Ramesh Krishnan ... [et al.] - Krishnan, Ramesh; Koe, Wei Loon; Othman, Rozana; Muthusamy, Geetha; Alias, Nurul Ezaili (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
Although much research attention has been given to study the effect of perceived job characteristics on various work outcomes, few have specifically examined the joint effect of perceived job characteristics and self-efficacy on employee work engagement. This study aimed to examine the role of self-efficacy as a moderator in the perceived job characteristics-work engagement relationship. A total of 646 employees from the healthcare sector in Malaysia participated in this study. A moderated hierarchical regression analysis revealed a positive effect of job characteristics (autonomy, skill variety, feedback, task significance, task identity) with work engagement and a significant interaction between task identity and self-efficacy in predicting employee work engagement. Managerial implications and directions for future research are discussed.